The Creed of Mundzirul Qoum and Mutafaqqih Fiddien in Shaping the Competence of Graduates from TMI Al-Amien Prenduan Islamic Boarding School - Zumrotus Sholihah; Ach. Nurholis Majid (Penerbit Hellow Pustaka, 2026)
Islamic boarding schools as Islamic educational institutions have a strategic role in forming cadres of scholars and leaders of the people. However, the dynamics of globalization present challenges, especially regarding how pesantren remain relevant in producing graduates who not only master religious knowledge (Mutafaqqih Fiddien), but also have leadership abilities (Mundzirul Qoum). This becomes important to study, considering that pesantren are faced with community expectations and the demands of the times. This study aims to describe the concepts of Mundzirul Qoum and Mutafaqqih Fiddien at Pondok Pesantren TMI Al-Amien Prenduan, analyze the implementation of these concepts, and explain their implications for the competence of pesantren graduates. The research focus includes three main aspects: (1) the concept of Mundzirul Qoum and Mutafaqqih Fiddien, (2) the implementation of the concept in shaping graduates, and (3) the implications of the concept on the competence of graduates. Analyzed data collection results a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation. Data analysis was conducted using an interactive analysis model, including: (1) data condensation, (2) data presentation, and (3) conclusion drawing and verification. Data validity was tested through triangulation of sources and techniques. The results showed that the concepts of Mundzirul Qoum and Mutafaqqih Fiddien are based on QS. At-Taubah: 122 and is implemented through various formal education programs, extracurricular activities, and habituation of Islamic values. This implementation includes the formation of santri character, mastery of religious and general knowledge, and leadership development. The implication of this concept is the creation of graduates who have intellectual, moral, and social competencies that are relevant to the needs of modern society.